1998
DOI: 10.1016/s0378-1097(98)00061-5
|View full text |Cite
|
Sign up to set email alerts
|

General transducing phages like Salmonella phage P22 isolated using a smooth strain of Escherichia coli as host

Abstract: A smooth colony strain, resistant to phages V and P22, was isolated from sewage and identified as Escherichia coli (strain H). Four temperate phages plaquing on strain H were isolated from sewage. The archetype, HK620, does not plaque on strains C and K12 of E. coli nor on the LT2 strain of Salmonella enterica. Bacterial mutants resistant to a clear plaque mutant of HK620 produce rough colonies. Some are also galactose-negative, a few are histidine auxotrophs, and most show sensitivity to V. HK620 can transduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 5 publications
(8 reference statements)
3
13
0
1
Order By: Relevance
“…4 A and B). We confirmed that like λ prophage, the HK620 prophage was also induced by mitomycin C (MMC), leading to a phage titer of 5 × 10 10 pfu/mL, similar to that obtained in the presence of BCM (3.5 × 10 10 pfu/mL) (26). By contrast, λ prophage was not excised in the presence of BCM, nor did it form infectious phage particles under the same conditions (Fig.…”
Section: Bcm Inhibition Of Rho Induces Prophage Hk620 In An Sos-indepsupporting
confidence: 82%
See 1 more Smart Citation
“…4 A and B). We confirmed that like λ prophage, the HK620 prophage was also induced by mitomycin C (MMC), leading to a phage titer of 5 × 10 10 pfu/mL, similar to that obtained in the presence of BCM (3.5 × 10 10 pfu/mL) (26). By contrast, λ prophage was not excised in the presence of BCM, nor did it form infectious phage particles under the same conditions (Fig.…”
Section: Bcm Inhibition Of Rho Induces Prophage Hk620 In An Sos-indepsupporting
confidence: 82%
“…We thus hypothesized that if prophage maintenance was controlled at the gene regulation level, the target should be the RDF gene. We tested and validated our prediction by using two different prophage models, KplE1 and HK620, which both integrate at the integration hot-spot argW in E. coli MG1655 and TD2158, respectively (25)(26)(27). KplE1 (also named CPS-53) is highly defective (it has only a 10-kb genome).…”
mentioning
confidence: 99%
“…For this purpose, CI proteins of many bacteriophages contain strong helix-turn-helix (HTH) motifs in their amino-terminal domains (24). Analysis of the deduced amino acid sequence of L11 with the program of Dodd and Egan (17) The L14 protein is highly homologous to the Roi proteins of bacteriophages HK620, H-19B, VT2-Sa, HK022, HK97, and 933W (16,33,37,43,52). In HK022, Roi causes phage propagation dependent on the integration host factor (IHF).…”
Section: Resultsmentioning
confidence: 99%
“…86 Phage P22, and presumably SP6, degrade the smooth portion of the lipopolysaccharide layer of S. typhimurium LT2, and coliphages similar to P22 that infect smooth E. coli strains have been isolated. 87 However, most laboratory strains of E. coli are rough and, consequently, most attention has been paid to rough-specific coliphages. This quirk of history in phage biology may have led to an under-appreciation of the role of virion-associated, polysaccharide-degrading enzymes associated with the degradation of polysaccharide capsules.…”
Section: Additional Commentsmentioning
confidence: 99%